Segmented versus Nonsegmented Deep-Brain Stimulation for Essential Tremor Differ in Ataxic Side Effects - Daniel A. Roque (Tremor and Other Hyperkinetic Movements, 2019)
Background: Directional, deep-brain stimulation may prove beneficial for targets (1) thinner along the lead trajectory, and (2) whose borders are not easily visible by neuroimaging. When targeting the ventral intermediate (VIM) nucleus of the thalamus for essential tremor, even baseline ataxia may be exacerbated by medial spread of current and antidromic stimulation of vestibular-cerebellar-thalamic afferents.